2010
DOI: 10.1088/0022-3727/43/50/505201
|View full text |Cite
|
Sign up to set email alerts
|

Probing photo-ionization: simulations of positive streamers in varying N2 : O2-mixtures

Abstract: Abstract. Photo-ionization is the accepted mechanism for the propagation of positive streamers in air though the parameters are not very well known; the efficiency of this mechanism largely depends on the presence of both nitrogen and oxygen. But experiments show that streamer propagation is amazingly robust against changes of the gas composition; even for pure nitrogen with impurity levels below 1 ppm streamers propagate essentially with the same velocity as in air, but their minimal diameter is smaller, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
130
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 41 publications
13
130
0
Order By: Relevance
“…It is generally found and understood that a higher applied electric field increases the streamer propagation velocity and that the velocities are in the range of 10 5 -10 7 m·s −1 [2,5,6,9,3,11,4,47,12]. Furthermore, various experiments show that negative streamers generally have a lower propagation velocity than positive streamers [12,48,47,45,40,10,6], which is surprising because negative streamers propagate through electron drift and positive streamers propagate against the electron drift through photoionisation (and to a lesser extent background ionisation) [9,38,49]. Therefore, for identical field enhancement at the streamer head, and a similar electron distribution, a negative streamer is expected to propagate faster [50].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally found and understood that a higher applied electric field increases the streamer propagation velocity and that the velocities are in the range of 10 5 -10 7 m·s −1 [2,5,6,9,3,11,4,47,12]. Furthermore, various experiments show that negative streamers generally have a lower propagation velocity than positive streamers [12,48,47,45,40,10,6], which is surprising because negative streamers propagate through electron drift and positive streamers propagate against the electron drift through photoionisation (and to a lesser extent background ionisation) [9,38,49]. Therefore, for identical field enhancement at the streamer head, and a similar electron distribution, a negative streamer is expected to propagate faster [50].…”
Section: Introductionmentioning
confidence: 99%
“…[17]. The detachment process [26,27], as well as photoionization [26,28], are simulated by assuming an initial background of electrons of n e ¼ 10 10 cm À3 at the pinhole region to ensure the possible propagation of a positive streamer.…”
Section: Initial Conditions Of Simulationmentioning
confidence: 99%
“…The production of various excited species and the increase of the electron density due to the passage of a streamer were simulated in several papers [3,[23][24][25][26][27][28][29][30][31][32][33], to name but a few, most of which agree that the electron density on the axis of the streamer is on the order of 10 13 − 10 14 cm − 3 . In general, the density of the excited species on the streamers axis will depend both on the neutral gas density and on the maximal electric field at the streamer tip.…”
Section: Introductionmentioning
confidence: 99%
“…We do not treat photo-ionization here, as several works demonstrated that this effect can be neglected at ground pressure. Photo-ionization may result in the breaking of scaling when laboratory streamers are compared with sprites [25,30,40].…”
mentioning
confidence: 99%